A Complete Guide to Writing Research Projects for Nursing, Rehabilitation, Healthcare Scholars and Professionals - Loveness A. Nkhata; Getrude Kakonya-Chifuka; Shadreck Thewo; Patricia Katowa-Mukwato; Margaret M. Mweshi (A Complete Guide to Writing Research Projects for Nursing, Rehabilitation, Healthcare Scholars and Professionals, 2025)
Purpose and Scope: This guide provides a framework for healthcare professionals navigating the research process from conceptualisation through dissemination. It equips nursing, rehabilitation, and healthcare scholars with practical methodologies for conducting effective research at any experience level. Content and Structure: The guide addresses research fundamentals (topic selection, question formulation, literature review); methodological approaches (study design, sampling, ethics); implementation (data collection, analysis, resource management); and dissemination strategies (reporting, presentations, publication). Target Audience and Value: This resource bridges knowledge gaps by providing guidance for both novice researchers with limited scientific backgrounds and experienced scholars seeking methodological refinement. By integrating research principles with practical examples, it enables readers to develop critical competencies, engage with scientific literature and contribute to healthcare knowledge and practice.